The Effect of Job Training on Employee Performance with Communication as an Intervening Variable in Hispicy Medan - Ramadhana, Sheihan; Isa Indrawan, Muhammad (SINOMIKA Journal: Publikasi Ilmiah Bidang Ekonomi dan Akuntansi, 2023)
This research aims to see the effect of job training on employee performance with communication as an intervening variable at Hispicy Medan. This research was conducted at Hispicy Medan, the type of research used was quantitative, the population of this study was 100 employees, and the sample used was the entire population at Hispicy Medan, namely 100 employees using a saturated sampling technique. The primary data source used in this research and uses a questionnaire to collect data, this research model uses analytical skills and the measuring tool is smart pls 3. The results of this research are as follows: Communication has a positive and significant effect on employee performance with an original sample value of 0.394 and P value 0.001. Job Training has a positive and significant effect on Employee Performance with the original sample of 0.519 and pvalues of 0.000. Job Training has a positive and significant effect on Communication with an original sample value of 0.894 and a P value of 0.000. Job Training has a positive and significant indirect effect on Employee Performance through Communication with an original sample value of 0.352 and a P value of 0.00.